Dynamic of accumulation and redistribution of various carbohydrate forms and nitrogen in organs of tomatoes under treatment with retardants - Rogach, V. V.; Kravets, O. O.; Buina, O. I.; Kuryata, V. G. (Regulatory Mechanisms in Biosystems, 2018)
The regulation of plant growth and development under application of antigibberellin compounds is accompanied by changes in the donor-acceptor system that in turn affects the accumulation and redistribution of carbohydrates and nitrogen-containing compounds. We studied the influence of tebuconazole 0.025% (EW-250) and 0.05% and 0.07% esphon (2-CEPA) on growth processes, leaf apparatus and content of various carbohydrate forms and total nitrogen content in vegetative organs of tomato hybrids Bobkat and Solerosso. A field-based micro-trial setup was established from 2013 to 2017. The plants were treated via foliar spraying with aqueous solution of retardants at the time of initiation of budding. Phytometric measurements were determined every 10 days, the content of various carbohydrate forms and total nitrogen in organs of plants was determined by using biochemical methods in a fixed dry material (the content of sugars and starch – by iodometric method, and the total nitrogen content – by Kjeldahl). It was found that both retardants reduced the linear growth of tomato plants. The results indicate that 2-CEPA treatment significantly decreased the plant height of both hybrids. Application of drugs increased the number of leaves per plant. The leaf dry matter weight increased, the most significant effect was created by EW-250. The leaf area of the retardant-treated tomatoes hybrid Solerosso increased and decreased in the hybrid Bobcat. Application of antigibberellin compounds intensified the outflow of sugars and remobilization of starch in roots and stems of both tomato hybrids. The content of starch, reducing and non-reducing sugars in leaves of hybrid Solerosso was higher after EW-250 treatment. 2-CEPA increased the content of reducing form of sugars, and EW-250 increased non-reducing form in the hybrid Bobkat. EW-250 intensified the accumulation of carbohydrates in fruits due to reducing sugars in both tomato hybrids, whereas 2-CEPA reduced their content compared with control. Growth inhibitors increased the starch content in fruits at the beginning of vegetation and intensified its reutilization at the end. This process was most intensive was in variant of EW-250-treated plants regardless of hybrids. We proved that there was a clear tendency to decrease the ratio of sugar content to starch in almost all organs of both tomato hybrids during the growing season. The most significant was the reduction of this ratio after EW-250 treatment. At the fruitification phase, the proportion of starch in retardant-treated plants increased compared to the control. The increased accumulation of carbohydrates in tomato fruits treated with EW-250 caused an increase in the average weight of the fruit. We have found that the total nitrogen content in vegetative organs decreased in the control and in the experimental variant of both tomato hybrids during vegetation. EW-250 accelerated the outflow of total nitrogen from roots and stems and increased its content in leaves. This drug retarded the accumulation of this element in fruit. Such changes in the dynamics of total nitrogen under the influence of tebuconazole resulted in enhanced formation of fruit on tomato plants. We concluded that the antigibberellin compounds EW-250 and 2-CEPA due the action on growth processes and leaf apparatus of tomato plants, changed the character of donor-acceptor relation through an increase in outflow of plastic substances from vegetative organs to fruits, which optimized the crop production.